Durable remissions in TCF3-HLF positive acute lymphoblastic leukemia with blinatumomab and stem cell transplantation - Mouttet, Brice; Kunz, Joachim (Haematologica, 2019)
TCF3-HLF -positive leukemia represents a rare subtype of childhood acute lymphoblastic leukemia (ALL), characterized by a high rate of treatment failure despite treatment intensification and allogeneic stem cell transplantation (SCT). Given the high and homogeneous expression of CD19 on blast cells
Published ahead of print on February 14, 2019
Gesehen am 07.10.2019